Ajaran Tarekat Alawiyah Dan Kontribusi Habib Abdullah Alawi Al-Haddad - Rangkuti, Miswar Rasyid (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2022)
The Alawiyah Tarekat is one of the tarekat that has received attention from various elements of society, characterized by the absence of allegiance in practicing its teachings, so that the Alawiyah Order has a tremendous influence on religious life, especially in Indonesia. This type of research uses a literature study or what is known as Library Research, where the references used are sourced from the treasures of the library in the form of scientific journals, books and so on. The current form of the Alawiyah tarekat teaching is a major contribution from Habib Abdullah Alawi al-Haddad, he formulated a merger of two tarekat teachings, namely Imam al-Ghazali's akhlaqi Sufism and Sunni Sufism from the Syadziliyyah tarekat. This change was because Habib Abdullah Alawi al-Haddad considered that the people at his time did not have the ability to practice the teachings of falsafi Sufism, because according to him the teachings of falsafi Sufism were only intended for those who had dived into the ocean of Sufism.